Minority consumption, savings, and investing analysis: consequences and implications. - Harper, Gabriel Duvall Jordan (Kansas State University, 2011)
The aim of this paper is to provide an analysis of the consumption, investing, and savings data across racial minority categories within the United States. This paper examines the three biggest minority racial categories within the United States. These three racial categories include Blacks, Asians, and Hispanics. Consumption patterns across minority groups are examined in Chapter 2. These patterns give insights into the annual purchasing decisions of Blacks, Asians, and Hispanics. Many of the choices in budget allocation to specific categories have consequences and implications that are explained at the end of this chapter. Chapter 3 focuses on savings characteristics of minority populations in the United States. 401k plans, IRAs, and other retirement plans are examined for different savings behaviors and rates across minority groups. This paper examines the savings attitudes and survey responses of participants to get a feel of the overall savings climate across racial groups. Chapter 4 examines the investment behaviors and attitudes of different minorities. The financial risk tolerance and portfolio composition of different minority groups are examined to gain insights into the large wealth gap between Whites and minorities in the United States. In addition, this paper examines the hypothesized reasons for the differences between racial categories in consumption, investing, and saving choices. In Chapter 5, I explore the different theories and assumptions presented in the literature on these topics in order to give the reader insight into why racial groups might make different consumption, investment, and savings decisions even when controlling for socioeconomic variables. The final chapter explains the consequences of consumption, investment, and savings decisions for the individual, the community, and the United States.
Keywords: Minority; Consumption; Savings; Investing; Consequences; Implications; Economics (0501)